Perencanaan Strategis Sistem Informasi untuk Optimalisasi Layanan Sekolah Menggunakan Ward and Peppard - Ibnur Rusi; Ferdy Febriyanto (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Abstract— The use of technology and information systems is an obligation that must be applied by every agency or organization to simplify and optimize operational implementation. Many agencies are actively using information systems so that the agency's performance can run well, systematically, and controlled, which will impact the credibility of their agency. A good information system can be created because of good planning. Strategic planning of information systems allows producing a good information system. This is because the output produced is in the form of strategic plans and documents that methodically describe the needs of information systems. Torsina Private Vocational School is a vocational school that seeks to implement information systems in every operation to improve schools' services. Therefore, strategic planning is needed in the development of IS/IT at Torsina Private Vocational Schools so that the implementation of information systems becomes more controlled and on target. IS/IT strategic planning in this study uses the Ward and Peppard model, while the analytical tools used are Critical Success Factors (CSF's), SWOT Analysis, Value Chain, and McFarlans Strategic Grid. The existence of an analytical tool is used to support the Ward and Peppard model to determine the internal and external environmental conditions of the organization. The results of this study are strategic planning of information systems at Torsina Private Vocational Schools in the form of business strategy, IT strategy, IS/IT management strategy, and an information system portfolio that is mapped based on the level of importance.